Gut commensal bacteria-derived polysaccharide sub-micron particles induce antigen-specific, tolerogenic responses - Harriman, Rian; Tu, Allen B.; Wang, Zhenyu; Radoc, Nicolas; Kakwere, Hamilton; Lewis, Jamal S. (Frontiers in Immunology, 2025)
Roughly 10.8% (>26 million) Americans suffer from food allergies (FA) which, in severe cases, can be life threatening. Oral immunotherapy (OIT) offers a promising allergen-specific approach in the management of FA. However, due to risk of anaphylactic shock, there are significant concerns regarding its safety and must be carried out in the hospital under careful supervision by clinicians. These concerns may be addressed through delivery of the allergen in engineered nanoparticulate packages which may additionally improve therapeutic efficacy. Polysaccharide A (PSA), a commensal-derived molecule produced by the gut-symbiont Bacteroides fragilis, has shown tremendous potency in ameliorating inflammatory diseases in various mouse models by eliciting tolerogenic T cell activity. The tolerogenic capacity in combination with its polymeric structure makes PSA an intriguing biomaterial for the formulation of tolerogenic sub-micron particles. We hypothesized that encapsulation of protein antigen within PSA sub-micron particles (SMPs) would provide a particle platform capable of inducing robust specific tolerogenic responses for safer treatment of FA. In this body of work, we demonstrate the successful fabrication of tolerance-inducing sub-micron particles using the commensal-derived molecule, PSA. We reveal that PSA sub-micron particles can be easily loaded with ovalbumin (OVA), a surrogate for protein allergens, resist degradation in gastric fluid, and induce OVA-specific tolerogenic responses. Taken altogether, our findings give credence that PSA SMPs are ideally suited for OIT applications. Moreover, this study demonstrates that PSA SMPs have the potential to serve as a “plug and play” system capable of inducing specific tolerance to any encapsulated antigen.